Continuous collection of pulse oximetry data: a new, inexpensive, portable computerized method. - Ronald, A L; Ramayya, G P; Chambers, W A (BJA: The British Journal of Anaesthesia, 1992)
The availability of reliable pulse oximetry equipment has led to interest in identifying patterns of hypoxaemia in the postoperative period. Methods for the computerized collection and analysis of pulse oximetry data have been described, but these require continuous use of a relatively powerful computer system throughout both the monitoring (data collection) and analysis periods. We have designed a technique which uses a small, portable and relatively inexpensive computer unit for data collection, after which the data may be transferred to a more powerful computer for analysis. Appropriate programming and choice of software have produced a relatively "user friendly" system which can be operated successfully even with minimal computing experience. The unit has the potential to be modified to form the basis of a "medical advice system" which could be used for the "intelligent" monitoring of high risk patients.